HADIS DI KALANGAN SUNNI (SHAHIH BUKHORI) DAN SYI’AH (AL-KAFI Al- KULAINI) - Khoirul Mudawinun Nisa' (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2016)
Sunnah or hadith has a unique and long history. He had experienced the transition from oral tradition to written tradition. The compilation also requires a fairly long time. Political competition among Muslims groups is also coloring in the context of the power struggle. Until the end of the 9th century, the codification effort can produce some great collections (hadith) which is considered to be authentic, in addition to a large number of other hadith collections. There is an assumption, that the belief differences in Islam streams impacted or even become the source of hadith differences that recognized by each group. For example Sunni groups just hold on a history of Sunni only, while Shi’ites only recognize the traditions of the history of Shi'ite only and so on. Study hadith among Sunni use the book of Saheeh Bukhari by Imam Bukhari and among Shi'ites use the book of al-kafi by al Kulaini, because both of books are famous books in the both of groups. Comparison of the two hadiths in both of them is assessed through: (1) systematic of the book contents; (2) method of the book preparation; (3) characteristics and features of the books; (4) quality of the book; (5) authentic level of the book; (6) criticisms and comments of the scholars. The results study showed that Al Kafi in the Shi’ite side is unequal footing with Sahih Bukhari on the Sunni side. Al Kafi has become a reference by Shi'ite cleric but no Shia scholar can prove that all of Al-Kafi history is Saheeh. In taking hadith as a reference, the Shia scholars would assess the position of hadith then set the fatwa. This is clearly different with Shahih Bukhari where Bukhari himself said that all of the hadiths are authentic, and has become the consensus of scholars (Sunni) that Sahih Bukhari is the most authentic book after the Qur'an.